Deletion of Non-histidine Domains of Histidine Kinase CHK1 Diminishes the Infectivity of Candida albicans in an Oral Mucosal Model - Feng, Yahui; Bian, Shaodong; Pang, Zhiping; Wen, Yiyang; Calderone, Richard; Li, Dongmei; Shi, Dongmei (Frontiers in Microbiology, 2022)
Objectives The histidine kinase (HK) CHK1 and other protein kinases in Candida albicans are key players in the development of hyphae. This study is designed to determine the functional roles of the S_Tkc domain (protein kinase) and the GAF domain of C. albicans CHK1 in hyphal formation and mucosal invasion. Methods The domain mutants CHK25 (ΔS_TkcCHK1/Δchk1) and CHK26 (ΔS_TkcΔgafCHK1/Δchk1) were first constructed by the his1-URA3-his1 method and confirmed by sequencing and Southern blots. A mouse tongue infection model was used to evaluate the hyphal invasion and fungal loads in each domain mutant, full-gene deletion mutant CHK21 (chk1Δ/chk1Δ), re-constituted strain CHK23 (chk1Δ/CHK1), and wild type (WT) from day 1 to day 5. The degree of invasion and damage to the oral mucosa of mice in each strain-infected group was evaluated in vivo and compared with germ tube rate and hyphal formation in vitro. Result When compared with severe mucosal damage and massive hyphal formation in WT- or CHK23-infected mouse tongues, the deletion of S_Tkc domain (CHK25) caused mild mucosal damage, and fungal invasion was eliminated as we observed in full-gene mutant CHK21. However, the deletion of S_Tkc and GAF (CHK26) partially restored the hyphal invasion and mucosal tissue damage that were exhibited in WT and CHK23. Regardless of the in vivo results, the decreased hyphal formation and germ tube in vitro were less apparent and quite similar between CHK25 and CHK26, especially at the late stage of the log phase where CHK26 was closer to WT and CHK23. However, growth defect and hyphal impairment of both domain mutants were similar to CHK21 in the early stages. Conclusion Our data suggest that both protein kinase (S_Tkc) and GAF domains in C. albicans CHK1 are required for hyphal invasiveness in mucosal tissue. The appropriate initiation of cell growth and hyphal formation at the lag phase is likely mediated by these two functional domains of CHK1 to maintain in vivo infectivity of C. albicans.